Software educativo sobre examen bucofacial para estudiantes de la carrera de Estomatología. - Jiménez Castellanos, María Isabel; Díaz Sánchez, Ledis Sabina; Paez Delgado, Delvis; Nicot Cos, Roberto Felipe; Lamour Ruiz, Dianelis (MEDISAN)
In the Dentistry major, the orofacial examination is a complex subject for students, due to the great amount of knowledge that must be taken into account for its accomplishment. This demands the use of teaching means that contribute to its study and understanding; mainly those elaborated from the Information and Communication Technologies. The great availability and variety of digital devices that exist in the student community, justified the development of an educational software for smart mobile devices as a resource for learning the orofacial examination, in the Dentistry major. The educational software was developed using the Mobincube program for Android and iOS operating systems, considering pedagogical, technical and economic criteria. The developed educational software constitutes a tool that facilitates the acquisition, integration and systematization of important knowledge in dentistry clinical practice, contributing to a better academic preparation of the future dentists.